(untitled) (Journal of Medicine, 2016)
Introduction: Population demography of the world including Bangladesh is on transition. The increasing number of elderly persons has a direct impact on the demand for health services due to the consequent rise in degenerative diseases of aging and changing life style. The chief objective was to know the median age of the medical inpatients. Methods: This was an observational study. It was conducted in the wards of Medicine department of Dhaka Medical College Hospital from the 1st of March to 15th March. Result: Median age of the admitted patients is 44.5 years. Highest admission is from the 6th to 8th decade of age group. A total of 176 patients (31.88%) were above the ageof 60 years. Discussion: Median age is one of the important measures of population aging. Global median age is 29 years whereas median age of Bangladeshi population is 22 years. The medianage of medical inpatients is relatively high. Percentage of patients aged more than 50 years are doubled in two decades. Conclusion: It is evident that the face of patients in medicine wards is growing older. We must redistribute our resources to deal the conditions and diseases prevalent to the elderly people. We must be kept our preparedness up to date to serve the senior citizens. J MEDICINE January 2016; 17 (1) : 27-29